The Influence of the Problem Based Learning Model on Student’ Learning Outcomes and Creative Thinking Abilities in Colloid Learning - Anna Juniar; Nestin Sundayan Zai; Pravil M Tambunan (Jurnal Pendidikan dan Pembelajaran Kimia, 2025)
This study was conducted to determine the effect of the Problem Based Learning model on students' learning outcomes and creative thinking skills on colloid material. This study used a pretest and posttest control group design. The sample in this study consisted of two classes, namely class XI IPA 2 with 34 students as the experimental class and class XI IPA 1 with 34 students as the control class determined using a purposive sampling technique. The learning outcomes and creative thinking abilities of students were measured through pretest and posttest and the average value of the learning outcomes and creative thinking abilities of students in the experimental class who were taught using the Problem Based Learning model was higher than the average value of the learning outcomes and creative thinking abilities of students in the control class who were taught using conventional learning. Hypothesis testing with independent sample t-test states that the first hypothesis value is obtained Tcount = 4.16 and it is known that Ttable = 1.99, then tcount tabet means that there is an influence of the Problem Based Learning model on learning outcomes. Furthermore, the second hypothesis is obtained Tcount = 10.85 and it is known that Ttable = 1.99, then Tcount>Ttable means that there is an influence of the Problem Based Learning model on students' creative thinking abilities. From this study it was found that the Problem Based Learning model has an influence on students' learning outcomes and creative thinking abilities on colloid material.